2018
DOI: 10.1029/2018je005582
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State of SiC at Extreme Conditions: New Insight Into the Interior of Carbon‐Rich Exoplanets

Abstract: There is a direct relation between the composition of a host star and that of the planets orbiting around it. As such, the recent discovery of stars with unusual chemical composition, notably enriched in carbon instead of oxygen, supports the existence of exoplanets with a chemistry dominated by carbides instead of oxides. Accordingly, several studies have been recently conducted on the Si–C binary system at high pressure and temperature. Nonetheless, the properties of carbides at the pressure‐temperature cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 76 publications
3
81
5
Order By: Relevance
“…Because of speculations of silicon carbide in exoplanetary interiors, physical properties of silicon carbide are being studied extensively at high pressures and temperatures (Wilson & Militzer 2014;Nisr et al 2017;Daviau & Lee 2017;Miozzi et al 2018). Significant amounts of silicon carbide in exoplanetary interiors would have a major impact on the thermal evolution and geodynamical processes on such exoplanets because its thermal conductivity is abnormally high (Nisr et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because of speculations of silicon carbide in exoplanetary interiors, physical properties of silicon carbide are being studied extensively at high pressures and temperatures (Wilson & Militzer 2014;Nisr et al 2017;Daviau & Lee 2017;Miozzi et al 2018). Significant amounts of silicon carbide in exoplanetary interiors would have a major impact on the thermal evolution and geodynamical processes on such exoplanets because its thermal conductivity is abnormally high (Nisr et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further work on this system, such as heating for longer time periods or quantifying the amount of C liberated as heating goes on, would aid in better understanding the breakup process of SiC and whether we are observing an incomplete exsolution of C from SiC or a complete decomposition of SiC. An alternative explanation for our observations is that the nonequimolar SiC y +(1 − y ) C phase is stable at the P‐T conditions explored here and that additional heating would not further liberate C. The hypothesis that SiC will continue to break up and fully decompose with continued heating, however, is supported by observations of SiC decomposition at ambient pressure (Bhaumik et al, ), as well as the lack of any observation of nonequimolar SiC in previous works (Miozzi et al, ).…”
Section: Discussionmentioning
confidence: 74%
“…Recent work has explored the SiC system at high P‐T through the LHDAC (Kidokoro et al, ; Miozzi et al, ; Nisr et al, ) and through shock experiments (Tracy et al, ). While we observe indication of SiC decomposition in our present experiments, as well as in previous measurements (Daviau & Lee, ), other studies probing similar conditions do not report the appearance of diamond diffraction or other indications of SiC decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Winn et al 2011) that could explain the observed ∼ 100 ppm modulation in the optical (Winn et al 2011;Dragomir et al 2014) and IR (Tamburo et al 2018) phase curves. Other proposed models for 55 Cancri e include the possibility of it being an icy planet (Zeng & Sasselov 2013;Zeng et al 2016) or having a carbon-rich composition (Madhusudhan et al 2012;Miozzi et al 2018). We understand that the situation concerning 55 Cancri e is complex as there is limited observational data that may appear contradictory in some occasions.…”
Section: Assumptions Used In Our Modelmentioning
confidence: 99%